Ready America - Haifisch, Anna 1986- (F.U. Press, 2024)
"Ready America takes us on a ride through a both strangely familiar and quite alien Los Angeles. Dogs in colorful sweatshirts, the glowing signs of a Vietnamese restaurant, solitary palm trees above the pavement. Packaging inscriptions, neon signs, and billboards fuse into an appealing typographic montage while familiar American icons peek out between stores and offices, clinics, and morgues. With her unmistakable wit, Anna Haifisch highlights the idiosyncrasies of a country in which catastrophes seem just as ordinary as the sight of a coyote in the Hollywood Hills. Full-color illustrations throughout"--Amazon.com
"Ready America was drawn between October 2022 and January 2023 in Los Angeles and Leipzig"
Keywords: Haifisch, Anna -- 1986-; Los Angeles (Calif.) / Comic books, strips, etc; National characteristics, American / Comic books, strips, etc; Advertising / Social aspects / Comic books, strips, etc; Commercial art / California / Los Angeles / Comic books, strips, etc; Graphic novels; Bildband